Impact of Congruence Between Sports Celebrity and Brand Personality on Purchase Intention: the Case of Mineral Water Category in Lithuania - Šeimienė, Eleonora; Jankovič, Tamara (Organizations and Markets in Emerging Economies, 2014)
In Lithuania as in other post-soviet and emerging countries, the practice of using celebrities in advertising is relatively new, but the trend has been growing over the past two decades. The study performed in Lithuanian mineral water category analyses relation between purchase intention of the advertised brand and such independent variables as sports celebrity, brand personality, celebrity similarity to the consumer and consumer attitude towards the celebrity. This paper proves that congruence between the celebrity and brand personality positively impacts purchase intention of the advertised brand. Brand personality turns to have the most impact on purchase intention. The study also revealed that the more consumers find themselves similar to the celebrity, the more they are willing to purchase the brand. However, consumer attitude towards the celebrity appears to be not as important as it was expected.
Keywords: celebrity; brand personality; purchase intention